Descentralização e participação na gestão de recursos hídricos: um estudo do comitê de bacia hidrográfica do recôncavo Norte-Inhambupe - Bahia - NUNES, Elizabete de Almeida (2014)
This paper discusses the factors that have influenced the feasibility of implementing the water resources management model, identifying a situation in which the committee is the North Reconcavo-Inhambupe Watershed (CBHRNI) in the state of Bahia, about of the decentralized management and participatory. The Law 9.433/97, known as the "Water Law", which established the National Policy of Water Resources, in which the basic principles have been established: the adoption of the watershed as a planning unit, recognition of water as an economic good; recognition of the multiple uses of water and management needs integrated, decentralized and participatory, a system based on the watershed committees. Although being innovative in its design this model has some limitations because the watershed management is still very incipient in several states. In addition to that, the marginalized portion of society lacks awareness in this pursuit for the inclusion in the right to participate. This is a descriptive and exploratory study realized in the CBHRNI, which occurred through direct observation, semi-structured interviews and questionnaires, with the participation of the members and the executive committee studied, using the method of qualitative analysis to facilitate descriptive analysis. The analyzes shows that the process of decentralization and participatory in the committee have positive aspects, but that difficult to measure. Extend the legitimacy of public choices, strengthen democracy and improve the conditions of governance and governability. But the model is not yet fully implemented, the decentralization does not work satisfactorily because the committee has not yet acquired autonomy, participative management has been wake. Also, the asymmetry of knowledge of the society representation at the committee and the lack of technical expertise to make certain decisions reduces the effectiveness of this participation.